2010
DOI: 10.1111/j.1749-6632.2010.05660.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of gonadotropins in the follicular phase

Abstract: Folliculogenesis in humans is a lengthy process that involves several regulators. Pituitary gonadotropins play crucial roles in the late stages, particularly in the last 15 days of follicle maturation. During the intercycle rise of follicle-stimulating hormone (FSH), selection of the dominant follicle takes place. This is a complex process that also involves locally produced substances. At the same time, luteinizing hormone (LH) stimulates the synthesis of androgens, which serve as the substrate for the produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 53 publications
1
24
0
1
Order By: Relevance
“…Ovarian follicles constitute the functional unit of the human ovary; endocrine signaling via the hypothalamus-pituitarygonadal axis is crucial for its survival, development, maturation and steroidogenic activity [1][2][3]. Nevertheless, local growth factors seem to have a pivotal and synergistic role in these procedures [4,5].…”
Section: Introductionmentioning
confidence: 98%
“…Ovarian follicles constitute the functional unit of the human ovary; endocrine signaling via the hypothalamus-pituitarygonadal axis is crucial for its survival, development, maturation and steroidogenic activity [1][2][3]. Nevertheless, local growth factors seem to have a pivotal and synergistic role in these procedures [4,5].…”
Section: Introductionmentioning
confidence: 98%
“…A growing body of evidence indicates that ovarian-secreted factors participate in these processes and function as either direct or indirect mediators downstream of LH signaling (5). Epidermal growth factor (EGF) is the founding member of the EGF family which also includes amphiregulin (Areg), epiregulin (Ereg), epigen, betacellulin (Btc), neuregulin and heparin-binding EGF-like growth factor (HB-EGF) (6).…”
mentioning
confidence: 99%
“…Primordial and primary preantral are considered gonadotropin independent stages of follicular development, since cumulus and theca cells lack FSH and LH receptors. However, studies have demonstrated the presence of FSH and LH receptors from the secondary preantral and from the antral stage onwards, respectively [3]. LH receptors are also present in the theca cells from the secondary preantral stage onwards, while they are lacking FSH receptors.…”
Section: Hcg and Assisted Reproductionmentioning
confidence: 99%